Estudio de la ganancia de peso en ganado bovino con suplementación alimenticia de panca de arroz y melaza. - Herrera Meza, Aldo Gabriel (2022)
This research dealt with the study of weight gain in cattle with food supplementation of rice paddy and molasses. Rice straw represents an important source of energy for cattle. For this reason, knowledge of the digestibility of this type of food is essential to establish the nutritional value and, therefore, the formulation of rations for ruminant animals. (Cedeño 2020). A roll of rice straw of approximately 500 kg, allows the maintenance of a wintering cow for more than a month in the corral, avoiding underselling the unproductive categories and maintaining the load for when the forage balance improves (Flores 2009). Molasses and molasses-urea supplements have notably influenced the production and reproductive capacity of cattle when the availability of forage and nutrients is reduced, as occurs in the dry season (Fernández 2014). The added value provided to crop residues such as rice paddy nourished with molasses positively favors the fattening and/or maintenance of cattle and also contributes to caring for the environment.